Efficacy and safety of lenalidomide in HIV-associated cryptococcal meningitis patients with persistent intracranial inflammation: an open-label, single-arm, prospective interventional study - Wan, Zhikai; Tao, Ran; Hui, Jiangjin; Liu, Xiang; Peng, Xiaorong; Guo, Yongzheng; Zhu, Xueling; Huang, Ying; Zhu, Biao (Journal of neuroinflammation, 2023)
Background Patients with human immunodeficiency virus-associated cryptococcal meningitis (HIV-CM) have persistent intracranial inflammation despite negative cerebrospinal fluid (CSF) fungal cultures after optimal treatment for CM, which could be devastating for the central nervous system. However, a definitive treatment strategy for persistent intracranial inflammation despite optimal antifungal therapies is undefined. Methods We identified 14 HIV-CM patients with persistent intracranial inflammation and conducted a 24-week, prospective, interventional study. All participants received lenalidomide (25 mg, p.o.) on days 1 to 21 of a 28-day cycle. Follow-up lasted for 24 weeks with visits at baseline and weeks 4, 8, 12, and 24. The primary endpoint was the change in clinical manifestations, routine CSF parameters, and MRI findings after lenalidomide treatment. An exploratory analysis was made on changes in cytokine levels in CSF. Safety and efficacy analyses were undertaken in patients who received at least one dose of lenalidomide. Results Of 14 participants, 11 patients completed the 24 weeks of follow-up. Rapid clinical remission following lenalidomide therapy was observed. Clinical manifestations (fever, headache, altered mentation) were reversed fully by week-4 and remained stable during follow-up. A significant reduction in white blood cell (WBC) count in CSF was noted occurred at week-4 ( P = 0.009). The median protein concentration in CSF decreased from 1.4 (0.7–3.2) g/L at baseline to 0.9 (0.6–1.4) at week-4 ( P = 0.004). The median albumin concentration in CSF decreased from 79.2 (48.4–149.8) mg/L at baseline to 55.3 (38.3–89.0) mg/L at week-4 ( P = 0.011). The WBC count, protein level, and albumin level in CSF remained stable and approached a normal range through week-24. There was no significant change in immunoglobulin-G, intracranial pressure (ICP), or chloride-ion concentration at each visit. Brain MRI demonstrated multiple lesions to be absorbed post-therapy. Levels of tumor necrosis factor-α granulocyte colony stimulating factor, interleukin (IL)-6, and IL-17A decreased significantly during 24-week follow-up. Two (14.3%) patients had mild skin rash, which resolved spontaneously. Lenalidomide-related serious adverse events were not observed. Conclusion Lenalidomide could improve persistent intracranial inflammation in HIV-CM patients significantly and was well tolerated without serious adverse events observed. And the additional randomized controlled study is required to further validate the finding.